Improvements in vision‐related quality of life in blind patients implanted with the Argus II Epiretinal Prosthesis. (25th August 2016) - Duncan, Jacque L; Richards, Thomas P; Arditi, Aries; da Cruz, Lyndon; Dagnelie, Gislin; Dorn, Jessy D; Ho, Allen C; Olmos de Koo, Lisa C; Barale, Pierre‐Olivier; Stanga, Paulo E; Thumann, Gabriele; Wang, Yizhong; et al.
Abstract : Background: The purpose of this analysis is to report the change in quality of life (QoL) after treatment with the Argus II Epiretinal Prosthesis in patients with end‐stage retinitis pigmentosa. Methods: The Vision and Quality of Life Index (VisQoL) was used to assess changes in QoL dimensions and overall utility score in a prospective 30‐patient single‐arm clinical study. VisQoL is a multi‐attribute instrument consisting of six dimensions (injury, life, roles, assistance, activity and friendship) that may be affected by visual impairment. Within each dimension, patients were divided into two groups based on how much their QoL was affected by their blindness at baseline (moderate/severe or minimal). Outcomes were compared within each dimension sub‐group between baseline and the combined follow‐up periods using the Friedman test. In addition, data from the six dimensions were combined into a single utility score, with baseline data compared to the combined follow‐up periods. Results: Overall, 80 per cent of the patients reported difficulty in one or more dimensions pre‐implant. Composite VisQoL utility scores at follow‐up showed no statistically significant change from baseline; however, in three of the six VisQoL dimensions (injury, life and roles), patients with baseline deficits showed significant and lasting improvement after implantation with Argus II. In two of the three remaining dimensions (assistance and activity), data trended toward an improvement. In the final VisQoL dimension (friendship), none of the patients reported baseline deficits, suggesting that patients had largely adjusted to this attribute. Conclusion: Patients whose vision negatively affected them with respect to three VisQoL dimensions (that is, getting injured, coping with the demands of their life and fulfilling their life roles) reported significant improvement in QoL after implantation of the Argus II retinal prosthesis. Furthermore, the benefit did not deteriorate at any point during the 36‐month follow‐up, suggesting a long‐term, durable improvement.